IMPLEMENTASI PENDIDIKAN KARAKTER BERBASIS PESANTREN DI MA PONDOK PESANTREN AL-HASANAH KABUPATEN BENGKULU TENGAH - Yeyen Mardanita (IAIN Bengkulu, 2018)
This research is motivated because of the increasing number of people’s negative behaviors that occur in everyday life, especially among school-age children such as drug use, sexual harassment, aggressive behavior, fights, bullying, deteriora- tion of religious tolerance and others.These negative behaviors are a sign that Indonesia is on the brink of collapse.It takes an education that can change the bad behavior for the better.Pondok Pesantren Al-Hasanah is an educational institution in which prioritize the formation of the personality and mental attitude of learners so that it has a good character and become the next generation of brilliant nation by instilling religious values and religious character.Based on the above background, then the formulation of the problem in this research is how the implementation of character-based pesantren education in MA Pondok Pesantren Al-Hasanah, what is the method of character education in Al-Hasanah Islamic Boarding School and what are the factors inhibiting and supporting the implementation of character education based on boarding school At MA Pondok Pesantren Al-Hasanah.This study aims to determine the implementation of character-based education boarding school in MA Pondok Pe- santren Al-Hasanah, to find out the method of character education based boarding school in MA Pondok Pesantren Al-Hasanah and to determine the factors inhibiting and supporting the implementation of character education based boarding school in MA Pondok Pesantren Al-Hasanah.This study is a qualitative research (qualitative research).Data collection is done by using obser- vation, interview, and documentation.With data collection steps, data reduction, data presentation, and conclusion.Based on the results of data analysis yag has been collected can be concluded that the implementation of character education in boarding school is applied in several values of character investing, among others: religious values, the value of independence and the value of responsibility.Character education method in boarding school Al-Hasanah implemented through several methods, namely: exemplary methods, methods of advice, methods of habituation, and the method of memorization.Factors inhibiting and supporting the implementation of character education based on boarding school in Pondok Pesantren Al-Hasanah Central Bengkulu Regency, among others:Not yet optimal sources of operational funds and constraints of the individual students them- selves, such as easily bored and undisciplined.While the supporting factors, among others, the existence of a sincere soul of the caregivers and ustadz / ustadzah and the existence of a dormitory system or accommodation for the santri